Precision tracking micro-pattern gaseous detectors at Budker Institute of Nuclear Physics. (1st July 2022) - Bobrovnikov, V.S.; Fedotovich, G.V.; Kaminskiy, V.V.; Kudryavtsev, V.N.; Maltsev, T.V.; Nikolaev, I.B.; Nikolenko, D.M.; Rachek, I.A.; Shekhtman, L.I.; Shestakov, Yu.V.; Sokolov, A.V.; Zakharov, S.A.; et al.
Abstract: In this article a short overview of current micro-pattern gaseous detectors development and applications at Budker Institute of Nuclear Physics is presented. The triple-GEM detector for the Laser Polarimeter facility and the end-cap discs for the upgrade of the CMD-3 detector are considered in more details.